Teaching beginner-level computational social science: interactive open education resources with learnr and shiny apps - Manyu Li (Frontiers in Education, 2023)
The article presents the use of open, inclusive pedagogical frameworks to develop a series of open education resources (OERs), specifically, interactive shiny web applications for teaching beginner-level computational social science (CSS) in undergraduate social science education. CSS is an emerging discipline that integrates data science methods with social science theories and research designs. However, undergraduate social science students could face a lack of a sense of STEM identity or belonging. Also, compared to STEM majors in natural science or engineering, average undergraduate social science students come in with limited mathematical or statistical knowledge. The OERs developed and tested in this article are designed with pedagogical frameworks that help overcome these barriers faced by students from diverse backgrounds and offer students a jump-start in learning CSS. This article presents the details of the tools, classroom implementation (in the form of a 6-week workshop series), the pedagogy frameworks applied, and the assessment methods and outcomes.